Effect of brefeldin A and the dynamics of the actin plate on cytokinesis of zygotes in the brown alga, Silvetia babingtonii (Fucales, Phaeophyceae). Issue 1 (2nd January 2019) - Nagasato, Chikako; Motomura, Taizo
ABSTRACT: In the cytokinesis of brown algae, actin filaments appear like a plate at the intersecting region of microtubules (MTs) that emerge from the centrosomes after mitosis. The function of the actin plate itself is still unknown. To elucidate the relationship between the actin plate, MTs and membrane fusion, without inducing cytoskeleton depolymerization, the effect of brefeldin A (BFA), which prevents the production of vesicles from Golgi bodies, was examined in zygotes of Silvetia babingtonii . The beginning of mitosis was slightly delayed in zygotes under BFA compared with the controls. Almost all zygotes were inhibited for the progression of cytokinesis by BFA treatment. Ultrastructural observations showed that Golgi cisternae became fragmented or curled following continuous treatment with BFA, and the inhibitory status of cytokinesis between zygotes. The next cell cycle started before cytokinesis was completed. Although the appearance of the actin plate was not disturbed by BFA treatment, the behaviour of the actin plate during the transition between the first and second cell cycles could be classified into two patterns: it was either invisible upon the initiation of the next cell cycle, or a portion of it remained even though the next cell cycle had begun. In the latter case, a part of the actin plate seemed to associate with the new partially formed cell partition membrane, and MTs from the centrosomes were bound to it. The actin plate completely disappeared in the next mitosis, then re-emerged in the middle area of the four daughter nuclei. The results of the present study indicated that, under BFA treatment, the actin plate persisted until just before the beginning of the next mitotic phase, when the new, incomplete cell partition membrane was present, and MTs sustained the actin plate until next mitosis.